In-Fiber Subpicosecond Pulse Shaping for Nonlinear Optical Telecommunication Data Processing at 640 Gbit/s. (4th January 2012) - Azaña, J.; Oxenløwe, L. K.; Palushani, E.; Slavík, R.; Galili, M.; Mulvad, H. C. H.; Hu, H.; Park, Y.; Clausen, A. T.; Jeppesen, P.
Abstract : We review recent work on all-fiber (long-period fiber grating) devices for optical pulse shaping, particularly flat-top pulse generation, down to the subpicosecond range and their application for nonlinear switching (demultiplexing) of optical time-division multiplexed (OTDM) data signals in fiber-optic telecommunication links operating up to 640 Gbit/s. Experiments are presented demonstrating error-free 640-to-10 Gbit/s demultiplexing of the 64 tributary channels using the generated flat-top pulses for temporal gating in a Kerr-effect-based nonlinear optical loop mirror. The use of flat-top pulses has critical benefits in the demultiplexing process, including a significantly increased timing-jitter tolerance (up to 500 fs, i.e., 30% of the bit period) and the associated improvement in the bit-error-rate performance (e.g., with a sensitivity increase of up to 13 dB as compared with the use of Gaussian-like gating pulses). Long-period fiber grating pulse shapers with reduced polarization dependence are fabricated and successfully used for polarization-independent 640-to-10 Gbit/s demultiplexing experiments.